MiR‐542‐3p controls hepatic stellate cell activation and fibrosis via targeting BMP‐7. Issue 3 (28th October 2018) - Ji, Feihong; Wang, Kuifeng; Zhang, Yu; Mao, Xin‐Li; Huang, Qin; Wang, Jun; Ye, Liping; Li, Youming
Abstract: There has been an increasing number of studies about microRNAs as key regulators in the development of hepatic fibrosis. Here, we demonstrate that miR‐542‐3p can promote hepatic fibrosis by downregulating the expression of bone morphogenetic protein 7 (BMP‐7), which is known to antagonize transforming growth factor β1 (TGFβ1)‐mediated fibrogenesis effect. The expression of miR‐542‐3p is increased in activated hepatic stellate cells (HSCs). Downregulation of MiR‐542‐3p by antisense inhibitors can inhibit HSCs activation markers, including α‐smooth muscle actin (α‐SMA) and collagen as well as TGFβ signaling pathways. MiR‐542‐3p was significantly upregulated in carbon tetrachloride (CCl4 )‐induced hepatic fibrosis in mice, and downregulation of miR‐542‐3p by lentivirus could prevent the development of hepatic fibrosis. In addition, miR‐542‐3p can directly bind to the 3′‐untranslated region of BMP‐7 mRNA, indicating that its profibrotic effect appears to be caused by its inhibition of BMP‐7. Our results suggest that downregulation of miR‐542‐3p prevents liver fibrosis both in vitro and in vivo, highlighting its potential as a novel biomarker or therapeutic target for hepatic fibrosis. Abstract : Downregulation of miR‐542‐3p prevents liver fibrosis both in vitro and in vivo. The profibrotic effect of miR‐542‐3p appears to be caused by its inhibition of bone morphogenetic protein 7 (BMP‐7), since miR‐542‐3p binds directly to the 3′‐untranslated region of BMP‐7 mRNA.